PENGARUH ASEAN-CHINA FREE TRADE AREA TERHADAP KOMODITI TEKSTIL INDONEISA PERIODE 2008-2015 - Raudah Aghnia Ahda; Made Siti Sundari; Idfi Setyaningrum (Jurnal Ekonomi dan Bisnis, 2019)
This study aims to determine whether there is different value between exportand import performance before ACFTA and after ACFTA by developing hypothesis from the previous studies. To test the proposed hypothesis, this Study employed the independent samples t-test with data from the World Bank database. The case study was carried out with concern on textile business between Indonesia and China. The results indicate that the exports value has different mean following the free trade agreement. Similar result occurs at the import value of textile from China toIndonesia.